1982
DOI: 10.1002/food.19820260112
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographie analysis of volatile sulphur‐containing compounds of salted and salted‐boiled pork

Abstract: The qualitative composition and quantitative ratios of the volatile sulphurcontaining compounds (VSCC) in salted and salted-boiled pork were studied by gas chromatography using the flame photometric detector. VSCC were isolated from the flavour condensate by treatment with mercuric chloride or extraction with diethyl ether. 27 VSCC were identified, including mercaptans, sulphides, polysulphides, heterocyclic compounds, as well as thioacid esters, with 12 of the compounds being detected in meat products for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Both 3-methylbutanal and 2-methylbutanal have recently been found to be volatile compounds in traditionally cured bacon (Andersen and Hinrichsen, 1994) and drycured ham (Parma ham) (Barbieri et al, 1992) and are often reported in other nitrite-cured meat products (Berdagué et al, 1991;Golovnya et al, 1982;Lillard and Ayres, 1969). 3-Methylbutanal has a powerful odor, which must be expected to influence the overall aroma in products, in which it is present. According to Shu and co-workers , 3-methylbutanal reacts at low temperature (~5 °C) with ammonium sulfide to form the compounds shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…Both 3-methylbutanal and 2-methylbutanal have recently been found to be volatile compounds in traditionally cured bacon (Andersen and Hinrichsen, 1994) and drycured ham (Parma ham) (Barbieri et al, 1992) and are often reported in other nitrite-cured meat products (Berdagué et al, 1991;Golovnya et al, 1982;Lillard and Ayres, 1969). 3-Methylbutanal has a powerful odor, which must be expected to influence the overall aroma in products, in which it is present. According to Shu and co-workers , 3-methylbutanal reacts at low temperature (~5 °C) with ammonium sulfide to form the compounds shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%